(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
China has realized the great importance and the great role of innovation in achieving distinguished industrial performance, so it began to support and encourage it in order to achieve this, and this is what this research tries to measure and prove through a standard study based on annual data for the period (1985-2020), and depending on the statistical program (Eviews 10). The research recommended some proposals, the most important of which are: China advancing the most important indicators of innovation by increasing spending on research and development and achieving the quality of domestic education for China and not on education abroad. Conformity and integration must be achieved between the most important indicators of innovation, especially with regard to human development (quality education) and patents. The model variables were (industrial performance log y) is the dependent variable. And (log x1 patents), (log x2 research and development spending), (log x3 education quality) and (log x4 technology progress), are the independent variables. The results indicated that the complete logarithmic model is the best among other models, and to achieve this goal the research relied on the assumption that innovation achieves distinguished industrial performance in both industrialized and emerging countries, including China. The support and encouragement of innovation indicators had a moral effect in achieving industrial performance in China and achieving economic and social well-being, but this depends on the country’s economic situation, strategies and laws adopted and the amount of gross domestic product allocated to support those indicators. Through the results of joint integration, the research concluded that there is a long-term equilibrium relationship and a short-term response between the research variables, and that there is a significant effect of some indicators and an insignificant effect of other indicators, in addition to the absence of the problem of self-correlation and the problem of heterogeneity of disparity. The research recommended some proposals, the most important of which is the need for China to raise the most important indicators of innovation by increasing spending on research and development and achieving the quality of local education for China rather than relying on education abroad. It is imperative to achieve harmony and integration between the most important indicators of innovation, especially with regard to human development (quality Education and patents) and among technological advances The research also recommended that Iraq should study this pioneering experience and make use of it as much as possible for the purpose of modernizing the Iraqi economy, The research also recommended conducting a future study of the industrialization experience in South Korea because it is a pioneering experiment that deserves to be studied and that it moved South Korea from a developing country to an advanced industrial country that competes with the advanced industrial countries.